2018
DOI: 10.1111/bjet.12607
|View full text |Cite
|
Sign up to set email alerts
|

Connecting game design with problem posing skills in early childhood

Abstract: This paper presents a teaching experiment with preschoolers, considering games as means for presenting problem‐based situations and focusing on the development of game design in connection to problem posing skills. The study was conducted in a focus group of eighteen 5–6‐year‐old students who participated in game design sessions, compared to a control group of students of the same age, who did not participate in any game design interventions. An experimental design research methodology was applied, where their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Coming from the fields of Human-Computer Interaction, user participation in the creation of the software that they will later use is realized through the field of participatory design [43]. In the context of designing DGBL activities, participatory design introduces learner-centricity, where different stakeholders, including designers, educators and students are members of the design process [44].…”
Section: Dgbl In Hementioning
confidence: 99%
See 1 more Smart Citation
“…Coming from the fields of Human-Computer Interaction, user participation in the creation of the software that they will later use is realized through the field of participatory design [43]. In the context of designing DGBL activities, participatory design introduces learner-centricity, where different stakeholders, including designers, educators and students are members of the design process [44].…”
Section: Dgbl In Hementioning
confidence: 99%
“…Several frameworks have been proposed for the examination and analysis of DGBL activities [34], [44]- [47], focusing on various aspects of DGBL, such as game design, learning experience, learning strategies, and systems design. Even if they approach the subject from different perspectives, using different approaches, there is a clear need for addressing both gaming and learning aspects in educational game design [20].…”
Section: Constructive Alignment In the Context Of Dgbl Educationmentioning
confidence: 99%
“…Mayer (1998) argued that problem posing can allow students to have positive attitudes toward course content and can enhance their metacognition abilities. Many studies have shown that the strategy of problem posing can allow students to engage in multi‐perspective thinking, which then boosts their abilities of critical thinking, creative thinking and reflection (Kalmpourtzis, 2019; Kopparla et al, 2019; Sung, Hwang, & Chang, 2016; Ye, Chang, & Lai, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, studies are investigating various aspects of problem posing (Akbaba Dağ & Kılıç Şahin, 2019;Chang, 2007;Gökkurt et al, 2015;Kalmpourtzis, 2019;Kavuncu, 2019;Korkmaz & Gür, 2006;Setiawan, 2016;Stayonova, 2005;Tertemiz & Sulak, 2013;Turhan & Güven, 2014). It is emphasized in the literature that problem-posing is a subject that teachers and mathematics educators ignore and that more research is needed to investigate this issue (Akay, 2006;Turhan & Güven, 2014).…”
Section: Introductionmentioning
confidence: 99%